Over-The-Phone Commuity Interpreting: A Corpus-Based Analysis of Interpreted Interactions in Community Settings - Boczarski, Przemyslaw (Research in Language, 2025)
This paper examines the under-researched field of Polish–English telephone interpreting, with particular focus on the interactional environment and methods of connection. It first outlines the emergence of telephone interpreting, considers its advantages and disadvantages, and then presents a summary of findings from a corpus study conducted in 2024, in which 250 Polish–English interpreting interactions were recorded and analysed with reference to the method of connection between parties and the sectoral distribution of topics or issues discussed in those interactions. As OPI is conducted exclusively through the auditory channel, interpreters are deprived of visual cues; consequently, each method of connection presents both benefits and drawbacks, with the three-way conference call emerging as the most effective format for telephonic interactions between Polish speakers who decide to use the services of Polish-English OPI interpreters.